2019
DOI: 10.1075/pbns.305.10san
|View full text |Cite
|
Sign up to set email alerts
|

Subjectivity and Causality in discourse and cognition

Abstract: Cognitively oriented linguists have various linguistic resources at their disposal, and therefore need to develop methodological strategies of when to use which method. This chapter illustrates the benefits of using converging evidence. We review research results from several methodologies, including the use of corpus-based, acquisition and processing d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 72 publications
0
1
0
Order By: Relevance
“…The distinction between subjective and objective causality in human cognition is substantiated by evidence from language development and processing (see [13] for a detailed review). For example, research on child language acquisition has shown that the acquisition of these two types of causality takes place at different ages, with objective causality being acquired earlier than subjective causality [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…The distinction between subjective and objective causality in human cognition is substantiated by evidence from language development and processing (see [13] for a detailed review). For example, research on child language acquisition has shown that the acquisition of these two types of causality takes place at different ages, with objective causality being acquired earlier than subjective causality [14,15].…”
Section: Introductionmentioning
confidence: 99%